Multimodal Blockade of the Renin-Angiotensin System Is Safe and Is a Potential Cancer Treatment for Cats - Munday JS; Odom T; Dittmer KE; Wetzel S; Hillmer K; Tan ST (MDPI (Basel, Switzerland), 2022)
The role of the renin-angiotensin system (RAS) in cancer growth and progression is well recognized in humans. However, studies on RAS inhibition with a single agent have not shown consistent anticancer effects, potentially due to the neoplastic cells utilizing alternative pathways for RAS activation. To achieve more complete RAS inhibition, multimodal therapy with several medications that simultaneously block multiple steps in the RAS has been developed for use in humans. In the present study, the safety of multimodal RAS inhibition using atenolol, benazepril, metformin, curcumin, and meloxicam was assessed in six cats with squamous cell carcinomas. Cats were treated for 8 weeks, with blood pressure measured and blood sampled five times during the treatment period. None of the cats developed hypotension, azotemia, or increased serum liver enzyme concentrations. The packed cell volume of one cat decreased to just below the reference range during treatment. One cat was reported to have increased vomiting, although this occurred infrequently. One cat was withdrawn from the study due to difficulties administering the medications, and another cat died of an unrelated cause. Two cats were euthanatized during the study period due to cancer progression. Two cats completed the 8-week study period. One was subsequently euthanized due to cancer progression while the other cat is still alive 32 weeks after entering the study and is still receiving the multimodal blockade of the RAS. This is the first evaluation of multimodal blockade of the RAS in veterinary species. The study showed that the treatment is safe, with only mild adverse effects observed in two treated cats. Due to the small number of cats, the efficacy of treatment could not be evaluated. However, evidence from human studies suggests that a multimodal blockade of RAS could be a safe and cost-effective treatment option for cancer in cats.
Keywords: cancer; cancer treatment; cat; oncology; renin-angiotensin system; therapy